Is there a “lost world” of criminal investigation? - Jones, David (American journal of criminal justice, 1984)
This article is a critical examination of current investigation textbooks. It argues that they, like urban government textbooks of years ago, are deficient in many ways. For instance it is asserted that in a number of respects current texts present an inaccurate depiction of the criminal investigation process. This comes about in a number of ways. For example, at least by implication, many texts appear to present an inaccurate portrayal of how investigators spend their time. Moreover, they also present a highly simplistic picture of both the inter- and intra-organizational context within which investigators must operate. In addition to these deficiencies, the texts under consideration are also guilty of over-emphasizing the role that criminalistics play in the investigative process, while at the same time under-emphasizing the role of informants. Furthermore, most texts put a heavy emphasis on describing the ideal investigator while ignoring the characteristics that actual investigators exhibit. Finally, it is suggested that because criminal investigation texts do not present typologies or categories of crime, the student is faced with a mass of facts that are difficult to learn and retain. The article concludes by suggesting a different framework for criminal investigation texts, a framework that emphasizes that investigators actually operate in an organizational setting which sets contsraints on their actions and a framework which uses a typology of investigative strategies.